Redes extracelulares de DNA de linfócitos T: Sua possível importância nas interações parasito-hospedeiro e na patogênese da leishmaniose tegumentar americana - Carolina Cattoni Koh (2019)
Cell death is critical to a variety of physiological functions, including protective or pathogenic immunity. The most studied mechanisms of cell death are apoptosis and necrosis. Apoptosis has well-defined and clear characteristics such as activation of the pathways of the caspases and the formation of apoptotic bodies. Necrosis is characterized by complete cell rupture. Etose is a mechanism of cell death, described in 2004, characterized by the release of extracellular traps (ETs), which are composed mainly of DNA and histones. ETs are able to trigger or amplify inflammatory responses and directly exert microbicidal activity. Cells of the innate immune response such as neutrophils, eosinophils and macrophages may release ETs, and it has been suggested that B and T lymphocytes may also be able to do so. Here we demonstrate, through the use of various techniques such as confocal, electron and scanning microscopies, flow cytometry, among others, that human CD4 + and CD8 + T cells are actually capable of releasing ETs. In addition, CD4 and CD8-derived ETs (which we have called LETs – “lymphocyte extracellular traps”) are morphologically and functionally distinct. Of particular interest are the facts that CD8-derived ETs connect distant cells, and co-localize with CD107a, a marker of vesicles containing cytotoxic granules. In addition, in this study, we have also demonstrated that lesions from patients with cutaneous and mucosal leishmaniasis also present ETs. These ETs are derived from CD8+ cells and co-localize with CD107+ vesicles, showing that CD8+ T cells release LETs in vivo. Our results suggest that LETs may emerge as a new strategy for the delivery of cytotoxic vesicles to distant target cells, providing new insights into mechanisms of CD8-mediated cell death and the pathogenesis of American tegumentary leishmaniasis.